Robert Wilson : 14 Stations. - Loers, Veit; Mennekes, Friedhelm; Wilson, Robert (München : Prestel Verlag, 2000)
In conjunctiion with the Oberammergau Passion Play 2000, the American artist Robert Wilson presents his interpretation of the 14 Stations of the Cross, from Christ being condemned, to the Resurrection.
biog. p. 62-63
Robert Wilson : 14 Stations, Oberammergauer Passionsspiele Oberammergau, May 21 - Oct. 8, 2000
Duits
Engels
boek
Keywords: Wilson, Robert